ANALISIS EFEKTIFITAS PENGGUNAAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN LAYANAN ADMINISTRASI PENDIDIKAN - Aminah, Sitti; Rahmah, Rahmah; Ismail, Imran (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the effectiveness of digital technology in enhancing educational administration services at UPT SMA Negeri 10 Wajo. Using a qualitative approach, data were collected through interviews, observations, and document studies with informants including the school principal, educators, students, the school committee, and parents. The findings indicate that digital technology improves administrative efficiency, particularly in data management, scheduling, school-parent communication, and academic reporting. Supporting factors include school policies, availability of digital devices, internet access, and educators’ openness to technology adoption. However, challenges such as limited digital literacy, infrastructure constraints, and technical issues remain obstacles. Recommended solutions include digital literacy training, infrastructure enhancement, and the development of a more user-friendly administrative system. Government support and active participation from parents and the school committee are essential in creating an effective and sustainable digital ecosystem.